Orientación vocacional desde las inteligencias múltiples - Escobar Rivas, Mayra Daniella (2025)
The study interprets vocational guidance through Howard Gardner’s theory of multiple intelligences, aiming to understand how this perspective can enrich the academic and professional guidance processes of secondary education students. A qualitative research design with a phenomenological–hermeneutic approach was employed, using in-depth interviews with four key informants from educational institutions in the state of Barinas (Venezuela). The inductive analysis, supported by Atlas.ti 24, identified categories such as approach to vocational guidance and multiple intelligences, revealing the need to align guidance practices with students’ diverse talents and cognitive styles. The findings show that incorporating the theory of multiple intelligences promotes a more personalized, reflective, and coherent approach to students’ life projects, contributing to their comprehensive academic and human development.